Higher Gradient Materials and Related Generalized Continua - Altenbach, Holm.; Müller, Wolfgang H.; Abali, Bilen Emek.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book discusses recent findings and advanced theories presented at two workshops at TU Berlin in 2017 and 2018. It underlines several advantages of generalized continuum models compared to the classical Cauchy continuum, which although widely used in engineering practice, has a number of limitations, such as: • The structural size is very small. • The microstructure is complex. • The effects are localized. As such, the development of generalized continuum models is helpful and results in a better description of the behavior of structures or materials. At the same time, there are more and more experimental studies supporting the new models because the number of material parameters is higher.
1 Several advantages of generalized continuum models compared to the classical Cauchy continuum -- 2 The development of generalized continuum models is helpful -- 3 The experimental efforts supporting the new models are steadily increasing.
Keywords: Materials -- Analysis; Mechanics, Applied; Solids; Mechanics; Characterization and Analytical Technique; Solid Mechanics; Classical Mechanics